Faktor-Faktor Risiko yang Berhubungan dengan Kejadian Taeniasis dan Sistiserkosis di Papua Barat - Semuel Sandy; Iman HS Sasto; Eva Fitriana; Evi Iriani Natalia (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2019)
Taeniasis and cysticercosis are zoonotic diseases pigs and still become a health problem in West Papua. In 2003-2004, the prevalence of taeniasis was 4.1% and cysticercosis 2.3%. The aim of the study was to determine the prevalence and determinants of transmission of the disease. A cross-sectional design was carried out in March-December 2016, with 1,489 of respondents. Data was collected through fingertip blood collection and interviews for determinant factors of taeniasis transmission and cysticercosis. Examination of blood samples was carried out using magnetic microparticle immunoassay. The results of the study on taeniasis proportion were 3.0% (n=1.489) and taeniasis determinant factors were education [RR=1.3; CI 95% (0.695-2.418); p=0.047], hand washing habits before eating [RR=12.3; CI 95% (5.857-25.853); p=0.0001], habit of washing hands after defecate (p=0.0001), consuming vegetables (p=0.0001), vegetables being washed in the river [RR=0.3; CI 95% (0.153-0.674); p=0.002] and consumption of roast meat [RR=0.3; CI 95% (0.166-0.570); p=0.0001]. The proportion of cysticercosis is 3.2% (n=1,489). and cysticercosis determinant factors are education [RR=0.3; CI 95% (0.162-0.819); p=0.011], hand washing habits before eating [RR=2.4; CI 95% (1.344-4.351); p=0.002], the habit of washing hands after defecate [RR=3.2; 95% CI (1.787-5.809); p=0.0001], nail hygiene [RR=2.8 CI 95% (1.415-5.546); p=0.002], consumption of vegetables [RR=0.3; CI 95% (0.179-0.577); p=0,0001], vegetables are washed in the river [RR=0.4; CI 95% (0.222-0.837); p=0.012]. Determinant factors of Taeniasis and cysticercosis were education level, hand washing, nail hygiene, consumption of vegetables, washing vegetables in the river and consumption of roasted meat. It is crucial to provide education to community about clean,healthy behavior, and consumption of cooked meat.